Avaliação antroposcópica e cefalométrica do perfil e da tendência facial e sua relação com as funções estomatognáticas - Pacheco, Andrielle de Bitencourt (2013)
Introduction: the profile and the facial tendency constitute the variation of bone and muscle structures of the individual, and may influence directly in the chewing, swallowing and breathing functions. Thus, the evaluation of these aspects is essential for Orofacial clinical work. The aim of this study was to investigate the correlation between the cephalometric and anthrophoscopic evaluation on the classification of profile and facial tendency, as well as to evaluate the association of these skeletal features with the functions of the stomatognathic system. Method: the sample consisted of 35 childrens, aged between six and twelve years, undergoing anthroposcopic evaluation with photographic documentation, with cephalometric and otorhinolaryngology evaluation. To verify the agreement between cephalometric and anthroposcopic evaluation was used the Kappa test. The association between profile and the facial tendency with the stomatognathic changes was analyzed using the Qui-square and Fisher Exact Test. Was adopted a significance level of p <0.05 for all tests. Results: the concordance among the judges in the classification of profile and the facial tendency was moderate. The concordance between the cephalometric and anthroposcopic evaluation as to profile was not possible as to analyze and the tendency was weak. Was observed good concordance between judges for the chewing variables and weak concordance for the swallowing variables. Was not found significant association between stomatognathic function and no association was found between stomatognathic functions with the facial profile and tendency. Conclusion: concludes that assessments and cephalometric antroposcópica differ and that changes stomatognathic not depend only on a few isolated variables.